Analytic hierarchy process applied in the prioritization of third-party logistics providers in banking services - Testoni, Paulo Siqueira [UNESP]; Tramarico, Claudemir Leif [UNESP]; Rodríguez, Elias Carlos Aguirre [UNESP]; Marins, Fernando Augusto Silva [UNESP] (FapUNIFESP (SciELO), 2024)
Paper aims: This paper describes research that aimed to develop a procedure for prioritizing the performance management of Third-party logistics (3PL) who work in a banking services company. Originality: This article’s main contribution is the development of a procedure for evaluation and prioritization of the main 3PL performance indicators based on the SCOR model’s metrics. Research method: This paper applied Analytic Hierarchy Process (AHP), a method for multi-criteria analysis, using the metrics of Supply Chain Operations Reference Model (SCOR). Main findings: The approach proposed evaluates performance indicators of 3PL and prioritizes the development of new performance indicators using the metrics agility, responsiveness, and reliability of SCOR. Implications for theory and practice: This research contributes to the literature by demonstrating the applicability of multicriteria approach to find the prioritization of 3PL in a banking services company.
Keywords: Analytic hierarchy process; Banking services; Performance management; Third-party logistics providers